Counting Box Learning Media Based on Local Wisdom: Innovation and Implications in Mathematics Learning in Elementary Education - Faizah, Maryam; Widayanti, Rena; Ridwan, Akhmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
One of the factors that causes students to have difficulty learning mathematics in addition to material is the need for more variety of media provided by teachers in learning. One effort that can be made to overcome students' learning difficulties is to develop additional learning media that suit the characteristics and needs of grade 1 students. The research aims to explain the process of developing local wisdom-based counting box media and analyze the attractiveness of the media. This research highlights local wisdom in Indonesia by using palm seeds to learn media. The research uses the Research and Development research method with the Borg and Gall development model, which adapts six stages. The research subjects were 15 students in class 1 at MI Ar-Rohmah. The validation results showed that the criteria were very valid and interesting. The validation results obtained a score of 98 from material experts, a score of 97 from media experts, and a score of 96 from learning experts. The level of media attractiveness was obtained from 15 student response questionnaires, with 92% of results indicating it was exciting.